(untitled) (Brazilian Journal of Radiation Sciences, 2022)
The use of nuclear technology is growing in Brazil, where it is possible to carry out the entire nuclear fuel cycle. This technology generates radioactive waste that must be treated before being released into the environment or stored in suitable facilities. Then, the first national repository - CENTENA - will be implemented, where all low and intermediate level radioactive waste generated in Brazilian territory will be safely stored. One of the barriers that will compose the repository will be composed of natural materials such as soils and clays, the latter for having a high adsorption and cation exchange capacities and swelling potential. The purpose of the article is to show the research carried out in Centro de Desenvolvimento da Tecnologia Nuclear (CDTN) with natural materials aiming their use in natural barriers. Four materials were characterized: CDTN soil, this soil with bentonite, expanded vermiculite and bentonite, using the clay characterization protocol. Primary mineralogical, physical and chemical analyzes were performed, such as X-ray diffraction, scanning electron microscopy, particle size distribution, specific surface area and cation exchange capacity. The results showed that these clays are potentially candidates for composing CENTENA’s natural barriers.